Gamification of Prosthetic Dentistry: A Denture Processing Card Game - Sanjay Hodar, Pratik; S. Sakpal, Omkar; Shankar Vyavaharr, Supriya; Laxman Shinde, Snehal; Pillewar, Anjusha; Rajan Kamat, Aishwarya (Journal of Neonatal Surgery, 2025)
N/A